Measuring Physical Activity in Children With Cochlear Implants Using Self-Reported PAQ-C Before and During the COVID-19 Pandemic - Ozgul Akin Senkal; Eyyup Kara; Ozan Senkal; Haydar Murat Yener (SAGE Open, 2021)
Physical inactivity is common during periods of self-isolation, but for children with special needs, there are crucial benefits to be gained from maintaining moderate to vigorous physical activity throughout the COVID-19 pandemic. This study aimed to compare the physical activity levels of children with cochlear implants and their typically developed peers before and during the COVID-19 pandemic. The sample included 135 children with cochlear implants and 105 typically developed peers. We compared the daily activity levels of the two groups, measured by a 10-item questionnaire and the triangulation method. Results of this study showed that the girls were less active than the boys. Most items had adequate variance, and their means were close to the center of the range of values. The PAQ-C scores for the children with cochlear implants were distributed across a wider range than the scores for the typically developed children. Children with cochlear implants were physically active during school hours but were less active outside school, spending 3 to 6 hours per day using digital media during the COVID-19 pandemic. Children with cochlear implants need to increase their physical activity in and out of school by increasing their level of independence and their ability to adapt to social life. Giving information about physical activity opportunities to parents of children with cochlear implants is an important issue. School presents an opportunity for children to engage in regular physical activity, which is beneficial for their health status.